Control of mycelial and carpogenic germination of Sclerotinia sclerotiorum (lib.)de Bary with essential oils from 17 plant species (Research, Society and Development, 2020)
Sclerotinia sclerotiorum is a phytopathogen that causes the disease known as Sclerotinia rot, present in many crops. It is necessary to deep the knowledge of the biology of the phytopathogen, it being an important tool is the evaluation of the viability of sclerodia. Since essential oils are being used for the control of phytopathogens, it could be tested in the myceliogenic and carpogenic germination of S. sclerotiorum together with controls with and without Tween. For myceliogenic germination, experiment was carried out in BDA medium and incubation in a BOD-type growth chamber at 18 ° C with 12-hour photoperiod. Germination evaluations were performed at 24, 48, 72 and 96 hours after the start of incubation. Carpogenic germination was induced in sterile soil and incubation in a growth chamber with a temperature of 18 ° C ± 2 C°, photoperiod of 12 hours and soil humidity at 100% of field capacity. The experimental design was completely randomized with 19 treatments, four repetitions. The oils of Eucalyptus citriodora, Cymbopogon citratus, Cinnamomum zeylanicum and Thymus vulgaris showed greater efficiency in the myceliogenic and carpogenic germination of Sclerotinia sclerotiorum.